The Sacrament of Baptism Fulfills A Longing for Salvation in The Mitoni Tradition: A Pastoral Circle Method - Rukmono, B Agus; Martasudjita, Emanuel Pranawa Dhatu (Journal of Asian Orientation in Theology, 2025)
Some Javanese Catholics still practice the mitoni tradition when a mother is seven months pregnant with her first child. It is believed that by carrying out this mitoni tradition, the birth process will be smooth and the mother and baby will be safe. Javanese Catholics often question whether or not mitoni is allowed according to the teachings of the Catholic Church. In this particular topic, the theological question arises as to whether it is still necessary to seek salvation through rituals, while salvation has been fully fulfilled through Jesus Christ and received in the Sacrament of Baptism. In answering this theological question, the author uses the literature study method as his research method.  The approach chosen to discuss the relationship between the mitoni tradition and the sacrament of Baptism is the pastoral circle method from the theory of Joe Holland Peter Henriot. Meanwhile, to analyze the mitoni ritual, the author uses Roland Barthes' semiotic theory. From the results of the analysis, noble values were found behind the mitoni tradition that are in line with Christian values. After these values are further examined with systematic reflection on the theological meaning of baptism, it is concluded that the mitoni tradition is very close to the tradition of baptism in the Catholic Church. Therefore, the mitoni tradition that is still carried out by Catholic Javanese can be preserved with some adjustments in accordance with the Catholic tradition.